Evidence against Resveratrol as a viable therapy for the rescue of defective ΔF508 CFTR - Jai, Ying (Biochim Biophys Acta, 2015)
BACKGROUND: Resveratrol, a natural phenolic compound, has been reported to rescue mutant ΔF508 CFTR in expression systems and primary epithelial cells. Although this implies a therapeutic benefit to patients with CF, investigations were performed using resveratrol concentrations greatly in excess of those achievable in plasma. We evaluated the efficacy of resveratrol as a CFTR corrector in relevant primary airway cells, using physiologically achievable resveratrol concentrations. METHODS: Cells expressing wt or ΔF508 CFTR were exposed to chronic or acute resveratrol. CFTR mRNA and protein expression were monitored. The effects of resveratrol on primary ΔF508 human airway cells were evaluated by equivalent current analysis using modified Ussing chambers. RESULTS: Consistent with previously published data in heterologous expression systems, high doses of resveratrol increased CFTR expression; however physiologically relevant concentrations were without effect. In contrast to heterologous expression systems, resveratrol was unable to increase mutant CFTR channel activity in primary airway cells. Elevated amiloride-sensitive currents, indicative of sodium transport and characteristically elevated in CF airway cells, were also unaffected by resveratrol CONCLUSIONS: High concentrations of resveratrol can increase CFTR mRNA and protein in some cell types. In addition, acute resveratrol exposure can stimulate CFTR mediated chloride secretion, probably by increasing cellular cAMP levels. Resveratrol at physiologically achievable levels yielded no benefit in primary ΔF508 airway cells, either in terms of amiloride-sensitive currents of CFTR currents.